Comparison of the Rate of Depression in Early and Late Elderly Women with Diabetes Mellitus - Fatmawati Fatmawati; Andi Suswani; Nurlina Nurlina (Jurnal Penelitian Pendidikan IPA, 2023)
Elderly people with Diabetes Mellitus (DM) have a greater risk of experiencing depression compared to the elderly who do not suffer from DM. The Ministry of Health divides the elderly into two categories based on age, namely the early elderly (46-55 years old) and the late elderly (56-65 years). Objective: to analyze the comparison of depression levels in early and late elderly women with DM. An analytic observational design with a cross-sectional approach. The sample in this study were 33 elderly (15 early elderly and 18 late elderly) with DM in two health centers, namely Bontobangun health center and Tanete health center, Bulukumba district. The level of depression was measured by the Depression Anxiety Stress Scales 21 questionnaire. Data analysis used the Pearson chi-square test with SPSS software. The early elderly tends to feel the level of mild depression (46.7%) even 6.7% of the early elderly do not experience depression. The late elderly tends to feel the level of severe depression (50%) even 5.6% of the late elderly have very severe depression. The results of statistical tests showed that there was a significant difference between the level of depression in the early elderly and the late elderly (p = 0.026). Women with DM aged 56-65 years are very susceptible to depression with a more severe level when compared to women with DM aged 46-55 years. The need for special treatment that makes the elderly as the main target to reduce the depression they experience